2007
DOI: 10.1101/lm.634607
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine infused into perirhinal cortex improves object recognition memory by blocking the acquisition of interfering object information

Abstract: In a previous study, we reported apparently paradoxical facilitation of object recognition memory following infusions of the cholinergic muscarinic receptor antagonist scopolamine into the perirhinal cortex (PRh) of rats. We attributed these effects to the blockade by scopolamine of the acquisition of interfering information. The present study tested this possibility directly by modifying the spontaneous object recognition memory task to allow the presentation of a potentially interfering object either before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 37 publications
7
26
0
1
Order By: Relevance
“…Our results further suggest that competitive interference between multiple memory systems may be present during the post-training period (consolidation phase) in the NOR task, as has been observed previously for other memory tasks (for review, see Schroeder et al 2002;Poldrack and Packard 2003;Stone et al 2005;Winters et al 2007). In contrast to the view suggesting a central role for the hippocampal system in memory formation generally, several studies have demonstrated that inactivation of the hippocampal structure does not induce a generalized amnesia, but rather causes impairments in specific types of memory.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results further suggest that competitive interference between multiple memory systems may be present during the post-training period (consolidation phase) in the NOR task, as has been observed previously for other memory tasks (for review, see Schroeder et al 2002;Poldrack and Packard 2003;Stone et al 2005;Winters et al 2007). In contrast to the view suggesting a central role for the hippocampal system in memory formation generally, several studies have demonstrated that inactivation of the hippocampal structure does not induce a generalized amnesia, but rather causes impairments in specific types of memory.…”
Section: Discussionsupporting
confidence: 84%
“…The hippocampus is required for contextual information processing, and multiple studies have shown that the perirhinal cortex is involved in the consolidation of object information (Brown and Aggleton 2001;Winters and Bussey 2005;Winters et al 2007). We have confirmed the requirement for the hippocampus in a spatial memory task and are the first to show that the object recognition memory is enhanced when the hippocampus is inactivated during the consolidation phase, implying that a normally functioning hippocampus may interfere with the process of object familiarization.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present findings also support the notion that the reactivation phase is not merely acting as a second sample phase in this paradigm. We and others have consistently shown that scopolamine administered prior to the sample phase causes robust learning impairments (Warburton et al 2003;Winters et al 2006Winters et al , 2007; however, prereactivation scopolamine in the present study caused no ** * * S RA (w/insert) C 72h 24h Figure 9. Intra-PRh scopolamine prevents novelty-induced destabilization of relatively remote object memories.…”
Section: Discussionmentioning
confidence: 41%
“…Our group and others have also previously demonstrated the involvement of the perirhinal cortex (PRh) in object memory reconsolidation (Romero-Granados et al 2010;Winters et al 2011;Balderas et al 2013). Given the established role of ACh in information encoding in the SOR task (Warburton et al 2003;Winters et al 2006Winters et al , 2007, we hypothesized that the novelty-induced object memory destabilization demonstrated in our previous study was triggered by cholinergic transmission at muscarinic receptors within PRh. Here we provide support for this hypothesis, showing that systemic and intra-PRh administration of muscarinic receptor antagonists or agonists prevent or facilitate object memory destabilization, respectively.…”
mentioning
confidence: 75%